Виявлення російської пропаганди у газеті "Вести" - Захарченко, Артем (Видавництво Львівської політехніки, 2015)
We proved fact of regular transmission of country-aggressor’s propaganda by Vesti newspaper. During the period of the research we revealed 30 cases of such a transmitting, approximately 2 statements in each edition. At the same time, in Day newspaper, for comparison, in this period only 3 such statements were retransmitted or average – 0,3 per day.
Keywords: пропаганда; газета "Вести"; інформаційна газета "День"; контент-аналіз; негативне зображення дійсності